Monocyte adaptations in patients with obesity during a 1.5 year lifestyle intervention - van der Valk, Eline S.; Mulder, Daniël S.; Kouwenhoven, Tessa; Nagtzaam, Nicole M. A.; van Rossum, Elisabeth F. C.; Dik, Willem A.; Leenen, Pieter J. M. (Frontiers in Immunology, 2022)
Background Obesity is associated with chronic, low-grade inflammation, which is reflected in altered peripheral blood monocyte characteristics. The aim of this study was to analyze the monocyte subset composition (classical (CM), intermediate (IM) and non-classical monocytes (NCM)), and their inflammatory marker profile (CD14, CD16, CD36, CD45, CD64, CD300e, HLA-DR) in individuals with obesity during a 1.5 year combined lifestyle intervention (CLI), comprising healthy nutrition, increased exercise and behavioral changes. Methods We analyzed monocyte subset counts and immunophenotypes in 73 individuals with obesity, and associated these to baseline body mass index (BMI) and waist circumference (WC). The measurements were repeated after 10 weeks and at the end of the intervention (1.5 years). Results Generally, monocyte subset counts were not associated to BMI or WC at baseline, neither did these change during the 1.5 year CLI. Immunophenotypically, higher baseline BMI and WC were associated to lower CD14 and higher CD300e expression by all subsets. During CLI there were remarkable changes in marker profiles: expression of CD14, CD36, CD45 and CD64 significantly decreased in CM and IM, as did CD16 (IM and NCM) (p<0.05). CD300e initially decreased after 10 weeks, but increased sharply at 1.5 years (all subsets). We observed no consistent associations between changes in monocyte characteristics and anthropometric changes. Conclusion A 1.5 year CLI in individuals with obesity mediates persistent immunophenotypic adaptations related to cellular activation in blood monocytes, whereas changes in subset distribution are limited. Lifestyle-induced changes in the inflammatory profile of monocytes differ from the ‘less-severe-obesity’-phenotype, suggesting a novel, ‘post-weight-loss’ monocyte setpoint.